2018
DOI: 10.1142/s0217732318502061
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the ρ(s) measurements by TOTEM at the LHC

Abstract: Implications of the recent measurements of the parameter ρ(s) (ratio of the real to imaginary parts of the forward scattering elastic amplitude) by TOTEM collaboration at √ s = 13 T eV are discussed with emphasis on the rising energy dependence of the ratio of elastic to total cross-sections.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The recent TOTEM results [4,5] generated a burst of high level and intense theoretical debate about the correct interpretation of these data, see Refs. [15][16][17][18][19][20][21][22][23][24][25][26][27]. All possible extreme views were present among these first interpretative papers, including claims for a maximal Odderon effect [23] and claims of lack of any significant Odderon effects, Refs.…”
Section: Odderonmentioning
confidence: 99%
“…The recent TOTEM results [4,5] generated a burst of high level and intense theoretical debate about the correct interpretation of these data, see Refs. [15][16][17][18][19][20][21][22][23][24][25][26][27]. All possible extreme views were present among these first interpretative papers, including claims for a maximal Odderon effect [23] and claims of lack of any significant Odderon effects, Refs.…”
Section: Odderonmentioning
confidence: 99%
“…The main motivation for this is our need to describe the energy behaviour of the ratio ρ = Re/Im of the scattering amplitude, to which the secondary reggeons make a significant contribution. The new TOTEM data [12] shows that the value of ρ = 0.1 ± 0.01(0.09 ± 0.01) is lower than expected, and this ignited the hot discussion about the possible contribution of the odderon [13][14][15][16][17][18][19][20]. The odderon contribution to the negative signature appears naturally in perturbative QCD, with an intercept which is equal to zero [21,22].…”
mentioning
confidence: 99%
“…The new data of TOTEM collaboration [1][2][3][4] drew attention to the state with negative signature and with an intercept which is close to unity (see Refs. [5][6][7][8][9][10][11][12][13][14]). This state is known as the Odderon, and it appears naturally in perturbative QCD (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[15] for the review) with the intercept α Odd (t = 0) = 1 [16,17]. In a number of papers it was shown that such a state could be helpful for describing the experimental data [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%